Performance of White-Clover Grasses Mixtures: Part-I Dry Matter Production, Botanical Composition, Nitrogen Use Efficient, Nitrogen Rate and Yield - IBRAHIM ERKOVAN, H.; TAN, MUSTAFA; BASRI HALITLIGIL, M.; KISLAL, HAKAN (Asian Journal of Chemistry, 2010)
In legume-grass mixtures, nitrogen relations are among the factors that affect the performance of the mixture. In this study, performance of the binary mixtures composed of white clover (Trifolium repens L.) with smooth bromegrass (Bromus inermis Leyss), orchardgrass (Dactylis glomerata L.) and red fescue (Festuca rubra L.), respectively was investigated in the establishment and following years. From a general point of view, mixtures were found to be more productive than white clover sown alone. In the establishment year, productivity of plants was reduced and the highest dry matter yield was obtained in the year following establishment. Higher yield in the following years was caused by increased grass species ratio in the mixture. Competitive strength of grass species was also found to be high in the following years. In the mixtures, where smooth bromegrass, grass species which has the highest competitive strength, takes place, legume ratio was found to be low and dry matter yield was high. The highest nitrogen content was determined to be in white clover sown alone while the highest nitrogen yield was observed in the mixture of white clover with smooth bromegrass.